Gastroschisis survival improvement and early intervention: experience in a developing country - Rahayatri, Tri Hening; Gunardi, Harsya Dwindaru; Amin, Rusdah Binti Muhammad; Tamba, Riana Pauline (Paediatrica Indonesiana, 2024)
Background Gastroschisis is the most common abdominal congenital defect worldwide. While the mortality rate is 5–10% in developed countries, the rate escalates in developing countries due to less access to surgical care, and studies on the condition are scarce. Gastroschisis mortality and morbidity rates in Indonesia are unknown or unclear; little is also known about influencing factors that reveal epidemiological characteristics. Objective To identify the rate and factors associated with gastroschisis mortality in Indonesia. Methods A retrospective cohort study was conducted at Dr. Cipto Mangunkusumo Hospital, which included neonates with gastroschisis who underwent defect closure surgery from January 2015 to September 2020. We explored possible influencing risk factors, including gestational age, birth weight, number of surgeries, age at closure, and presence of gastroschisis complications. Bivariate analysis was done using Chi-square or Fisher’s test. Results Of 49 neonates with gastroschisis, 42 were included in the study. Seven neonates were excluded due to incomplete medical records. The mortality rate of gastroschisis based on our data was 69%. The age at closure (<1 day) was significantly associated with lower mortality rate (P=0.005). In contrast, other factors, including gestational age, birth weight, number of surgeries, and the presence of complicated gastroschisis were not the risk factors of gastroschisis mortality. Conclusion The mortality rate of gastroschisis is high in Indonesia, specifically at Dr. Cipto Mangunkusumo Hospital. Immediate closure is significantly associated with a decreased likelihood of death. Awareness, diagnosis, and efficient referral of gastroschisis from remote areas to a tertiary facility must be encouraged to reduce the high mortality rate.